Hubungan Ekspor - Produk Domestik Bruto (PDB) di Sektor Pertanian Indonesia - Fitria Dewi Raswatie (Journal of Agriculture, Resource and Environmental Economics, 2014)
The agricultural sector has an important role in developing economy as a contribution for the national Gross Domestic Product (GDP). Thus, it iimportant to see agricultural export related to agricultural GDP. Structural change caused by economic crisis is also important to be observed in terms of its influence toward variables in the agricultural sector. This research functions to: (1) Analyze short term and long term relations between agricultural export and GDP of the agricultural sector and other variables in Indonesia’s agricultural sector; (2) Analyze structural in Indonesia’s agricultural sector. The method used is ECM model and Chow Test. Agricultural GDP has a different relation towards agricultural export in short term and long term. Then, there was a structural change caused by economic crisis in 1997. Estimation result after added by monetary crisis dummy in 1997 shows that in short term, agricultural GDP one year previously, agricultural TFP, agricultural domestic price, agricultural export price, agricultural domestic price one year previously, and economic crisis dummy of 1997 have significant influences toward agricultural export. Analysis of the new ECM result (short term) showst that the parameter coefficient signs of the following variables: agricultural GDP, agricultural TFP, agricultural domestic price, agricultural export price, in accordance with the hypothesis are variables with a one year lag. There is a lag of agricultural export in response to the influencing variables.